Strategi Peningkatan Daya Saing UMKM Pengolahan Bandeng di Desa Jarangan, Kecamatan Rejoso (Menggunakan Analisis SWOT) - Muh. Bagus Wijaya; Nurul Lathifah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The development of milkfish processing businesses in Jarangan Village, Rejoso District has great potential due to the abundance of raw materials and the skills of the community. However, challenges such as limited capital, market access, and human resources still hinder progress. Through a SWOT analysis, a development strategy was formulated that includes skills training, increased access to capital, product diversification, and the utilization of digital technology for marketing. Support from the government and collaboration among business actors are crucial to optimizing this potential. With the right strategic measures, it is hoped that the processing of milkfish in Jarangan Village can significantly contribute to local economic growth and improve the welfare of the community.